Pengaruh Kompetensi Pedagogik Guru dan Motivasi Kerja terhadap Kinerja Mengajar Sekolah Dasar Negeri - Aminan Aminan; Rahmatullah Rahmatullah; Akmaluddin Akmaluddin; Siti Mayang Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of teacher pedagogical competence and work motivation on the teaching performance of state elementary school teachers in Bakongan Timur District, South Aceh Regency. The approach used in this research is a quantitative approach with an associative type of research. The results of the study prove that the Pedagogical Competence variable (X1) is 4.971 with a t table of 1.675, indicating that t count > t table (4.971 > 1.675), with a significant value (0.000 < 0.05) so that teacher pedagogical competence (X1) partially influences significant to teacher performance (Y) and the teacher work motivation variable (X2) of ) of 2.206 with a t table of 1.675 shows that t count > t table (2.206 > 1.675), with a significant value (0.002 < 0.05) so that teacher work motivation (X1) partially has a considerable influence on teacher performance (Y). With the calculated F value and F table or calculated F value of 19.109 > 2.786 and a significant probability of 0.000 < 0.05. The conclusion is that the variables of pedagogical competence and teacher work motivation have a simultaneous influence on teacher performance variables in state elementary schools in Bakongan Timur District, South Aceh Regency. South Aceh Regency. Keywords: Pedagogical Competence, Teaching Performance, Work Motivation